Evaluation of the Antibacterial Activity of Ethanol Versus Hydroalcoholic Extract of Mangifera indica Linn Leaves in Different Concentrations Against Streptococcus Mutans - An In Vitro Study - B.K. Lilly; G.M. Prashant; V.H. Sushanth; Mohamed Imranulla; C.R. Allamaprabhu; H.P. Vivek (Indian Journal of Dental Research)
Aim: To evaluate the antibacterial activity of ethanolic extracts and hydroalcoholic extracts of Mangifera indica Linn (mango) plant leaves on Streptococcus Mutans in comparison with the positive control (chlorhexidine 0.12%) and negative control (alcohol 96%). Settings and Design: Ethanolic and hydroalcoholic extracts of Mangifera indica Linn leaves were obtained by following the extraction procedure. A disc diffusion test was carried out for each group on Streptococcus Mutans. Materials and Methods: In brain heart infusion agar, Mangifera indica ethanol extract (MEE) and Mangifera indica hydroalcoholic extract (MHE) at 100% and 25% were applied to S. mutans cultures in comparison to the positive (chlorhexidine 0.12%) and negative (alcohol 96%) control groups. For every study group, cultures were produced using the Kirby-Bauer diffusion method, and incubating the cultures at 37°C for 24 hours. Statistical Analysis Used: The data were analysed using two-way ANOVA followed by a post hoc test. Result: It was found that the MHE 100% and 25% had a higher antibacterial activity of 27.8 ± 1.7 mm and 21.8 ± 1.0mm at 75 µg/ml, respectively compared to other groups. Extracts were found to have statistically significant (P ≤ 0.05) antimicrobial activity against Streptococcus Mutans. Conclusion: All the six groups used in the present study showed antibacterial efficacy and were effective against Streptococcus Mutans. Chlorhexidine continues to remain the gold standard. In comparison with control groups and extracts, MHE 100% showed a maximum zone of inhibition (27.8 ± 1.7 mm at 75 µg/ml) followed by other groups with statistically significant differences. Hence the herbal alternatives proved to be an effective and safe alternative and can be used as conventional modes of treatment.